Rate-Distortion Optimal Video Transport Over IP Allowing Packets With Bit Errors - Harmanci, O.; Tekalp, A.M. (IEEE transactions on image processing, 2007)
We propose new models and methods for rate-distortion (RD) optimal video delivery over IP, when packets with bit errors are also delivered. In particular, we propose RD optimal methods for slicing and unequal error protection (UEP) of packets over IP allowing transmission of packets with bit errors. The proposed framework can be employed in a classical independent-layer transport model for optimal slicing, as well as in a cross-layer transport model for optimal slicing and UEP, where the forward error correction (FEC) coding is performed at the link layer, but the application controls the FEC code rate with the constraint that a given IP packet is subject to constant channel protection. The proposed method uses a novel dynamic programming approach to determine the optimal slicing and UEP configuration for each video frame in a practical manner, that is compliant with the AVC/H.264 standard. We also propose new rate and distortion estimation techniques at the encoder side in order to efficiently evaluate the objective function for a slice configuration. The cross-layer formulation option effectively determines which regions of a frame should be protected better; hence, it can be considered as a spatial UEP scheme. We successfully demonstrate, by means of experimental results, that each component of the proposed system provides significant gains, up to 2.0 dB, compared to competitive methods